National report of blood lead levels and lead-glazed ceramics use in vulnerable children - Martha María Téllez-Rojo; Luis F Bautista-Arredondo; Belem Trejo-Valdivia; Alejandra Cantoral; Daniel Estrada-Sánchez; Rubén Kraiem; Ivan Pantic; Antonio Rosa-Parra; Luz María Gómez-Acosta; Martín Romero-Martínez; Lucía Cuevas-Nasu; Teresa Shamah-Levy; et al. (Instituto Nacional de Salud Pública, 2019)
Objective. To estimate the prevalence of elevated (≥5.0μg / dL) blood lead levels (BLL) and its association with the use of lead glazed ceramics (LGC). Materials and methods. In 2018, we measured capillary BLL in a representative sample of children 1 to 4 years old residing in Mexican localities under 100 000 inhabitants (Ensanut 100k). We inquired about use of LGC for food preparation and consumption. To estimate its association with BLL, multinomial logit models stratified by region were generated. Results. The prevalence of elevated BLL levels was 21.8%. For the North, Central and South regions, the prevalence were 9.8, 20.7 and 25.8%, respectively. The association with use and frequency of LGC was highly significant and differential by region. Conclusions. Lead exposure remains a public health problem in Mexico, particularly in the Central and South regions, and is strongly associated with the use of LGC.